Experiences of homosexual patients' access to primary health care services in Umlazi, KwaZulu-Natal - Nokulunga H. Cele; Maureen N. Sibiya; Dudu G. Sokhela (AOSIS, 2015)
Background: Homosexual patients are affected by social factors in their environment, and as a result may not have easy access to existing health care services. Prejudice against homosexuality and homosexual patients remains a barrier to them seeking appropriate healthcare. The concern is that lesbians and gays might delay or avoid seeking health care when they need it because of past discrimination or perceived homophobia within the health care thereby putting their health at risk. Aim of the study: The aim of the study was to explore and describe the experiences of homosexual patients utilising primary health care (PHC) services in Umlazi in the province ofKwaZulu-Natal (KZN). Method: A qualitative, exploratory, descriptive study was conducted which was contextual innature. Semi-structured interviews were conducted with 12 participants. The findings of this study were analysed using content analysis. Results: Two major themes emerged from the data analysis, namely, prejudice against homosexual patients by health care providers and other patients at the primary health care facilities, and, homophobic behaviour from primary health care personnel. Conclusion: Participants experienced prejudice and homophobic behaviour in the course of utilising PHC clinics in Umlazi, which created a barrier to their utilisation of health services located there. Nursing education institutions, in collaboration with the National Department of Health, should introduce homosexuality and anti-homophobia education programmes during the pre-service and in-service education period. Such programmes will help to familiarise health care providers with the health care needs of homosexual patients and may decrease homophobic attitudes.